Natuna Off-Shelf Current (NOC) Vertical Variability and Its Relation to ENSO in the North Natuna Sea - Hariyadi Hariyadi; Johannes Hutabarat; Denny Nugroho Sugianto; Muhammad Faiq Marwa Noercholis; Niken Dwi Prasetyarini; Widodo S. Pranowo; Kunarso Kunarso; Parichat Wetchayount; Anindya Wirasatriya (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
During the northwest monsoon (NWM), southerly flow off the Natuna Islands appeared as the extension of the turning Vietnam coastal jet, known as Natuna off-shelf current (NOC). NOC is generated by the interaction of wind stress and the North Natuna Sea’s bottom topography. The purposes of the present study is to investigate the vertical variability of NOC and its relation to El Niňo Southern Oscillation (ENSO) using Marine Copernicus reanalysis data. The vertical variability refers to the spatial distribution of NOC pattern at the surface layer, thermocline layer, and deep/bottom layer.  in 2014 as representative of normal ENSO condition. To investigate the effect of ENSO, the spatial distribution of NOC in 2011 and 2016 were compared which represent the La Niňa and El Niňo conditions, respectively. The results show that NOC starts to generate at the southeast monsoon season to the transition I season and peaks in the northwest monsoon season. The occurrence of NOC is identified at all depth layers with the weakened NOC at the deep layer. Related to the ENSO effect, La Niňa tends to strengthen NOC while El Niňo tends to weaken NOC. These are releted with the strengthening and weakening northerly wind speed during La Niňa and El Niňo, Respectively. During La Niňa events, the NOC occurs more frequently than during El Niňo. Thus, beside affecting the magnitude of NOC, ENSO also influence the frequency occurrence of NOC.